Competitiveness, clusters and policy at the regional level: Rhetoric vs. practice in designing policy for depressed regions - Argentino Pessoa (European Regional Science Association (ERSA), 2010)
This paper reviews the most important theoretical foundations of the spatial competitiveness conception, dealing with three levels of competitiveness: the country, the region and the tourism destination. Consequently, it draws attention to the main aspects that such concepts of competitiveness must include and it links the regional competitiveness with the related concept of cluster. Therefore, section 2 reviews the key aspects of competitiveness at the first level highlighting the role of the main forces acting at the national level. Section 3 extends the concept to the regional level, highlighting the critical aspects that must be considered when policy tries to increase the competitiveness of a particular region. Section 4 analyses the possibilities of extending the competitiveness concept to tourism destinations. Next, the paper analyses the literature on policy advice and discuss the inconsistency between the theory and the policy designed to promote regional competitiveness. Finally, the paper presents some concluding remarks on regional policy applied to depressed regions.
Keywords: Q25; Q28; R19; R58; 330; clusters; competitiveness; regional policy; tourism